2012
DOI: 10.1073/pnas.1207293109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of S-phase kinase-associated protein 2 (Skp2) reprograms and converts diabetogenic T cells to Foxp3 + regulatory T cells

Abstract: Autoreactive pathogenic T cells (Tpaths) and regulatory T cells (Tregs) express a distinct gene profiles; however, the genes and associated genetic/signaling pathways responsible for the functional determination of Tpaths vs. Tregs remain unknown. Here we show that Skp2, an E3 ubiquitin ligase that affects cell cycle control and death, plays a critical role in the function of diabetogenic Tpaths and Tregs. Down-regulation of Skp2 in diabetogenic Tpaths converts them into Foxp3-expressing Tregs. The suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Consistent with a previous study that examined possible related signaling pathways shared in the pathogenesis of several systemic autoimmune diseases (SAID) such as dermatomyositis, polymyositis, rheumatoid arthritis, and SLE, a subset of five viral-related differentially expressed genes (i.e., RSAD2, IFIT3, ISG15, STAT1, and EIF2AK) was detected in peripheral blood of SAID probands and their unaffected twins ( 50 ). Additionally, other genes that were identified in our study, including BCL2, OAS1, MX1, and SKP2 have been previously associated with various autoimmune diseases ( 51 54 ). Therefore, our findings further suggest that these common IFN signature genes are shared across multiple autoimmune diseases including pemphigus and SLE.…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with a previous study that examined possible related signaling pathways shared in the pathogenesis of several systemic autoimmune diseases (SAID) such as dermatomyositis, polymyositis, rheumatoid arthritis, and SLE, a subset of five viral-related differentially expressed genes (i.e., RSAD2, IFIT3, ISG15, STAT1, and EIF2AK) was detected in peripheral blood of SAID probands and their unaffected twins ( 50 ). Additionally, other genes that were identified in our study, including BCL2, OAS1, MX1, and SKP2 have been previously associated with various autoimmune diseases ( 51 54 ). Therefore, our findings further suggest that these common IFN signature genes are shared across multiple autoimmune diseases including pemphigus and SLE.…”
Section: Discussionsupporting
confidence: 53%
“…Formation of dnIKK2-Treg-EV-converted Treg could be explained by the link coupling cell cycle regulation and Treg differentiation provided by data that human CD4 + CD25 − T cells treated with anti-CD3/anti-CD28 together with the vasoactive intestinal peptide underwent cell cycle arrest and acquired T cell suppressive activities 52 . Moreover, the down-regulation of cell cycle and Foxo family genes resulted in reprogramming and the conversion of diabetogenic autoreactive T cells to Treg that did not need cell-to-cell contact with target cells 53 , similarly to dnIKK2-Treg-EV-converted Treg here described. Furthermore, modulating cell cycle in T cells plays a role in acquired peripheral tolerance to alloantigens 54 , as Treg from cdk-2-deficient mice display enhanced immunosuppressive function and cdk-2-deficient mice failed to reject a cardiac allograft due to the presence of fewer Th1 and more Foxp3 + Treg in tolerated grafts compared to rejected grafts from wild type recipients 55 .…”
Section: Discussionmentioning
confidence: 64%
“…Wang et al indicated that depletion of Skp2 led to up-regulation of p27 and p21 in autoreactive pathogenic T cells (Tpaths) [ 17 ]. Skp2-repression also increases expression of Foxp3, a key transcription factor in the control of regulatory T cells (Treg) which suppresses induction and proliferation of the effector T cells [ 18 ] and induces the conversion of Tpaths into regulatory T cells (Treg) producing IL-10.…”
Section: Discussionmentioning
confidence: 99%